2021
DOI: 10.1186/s12935-021-01920-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and angiogenesis: a new era for the management of colorectal cancer

Abstract: MicroRNAs (miRNAs) are a class of small noncoding RNA molecules containing only 20–22 nucleotides. MiRNAs play a role in gene silencing and translation suppression by targeting and binding to mRNA. Proper control of miRNA expression is very important for maintaining a normal physiological environment because miRNAs can affect most cellular pathways, including cell cycle checkpoint, cell proliferation, and apoptosis pathways, and have a wide range of target genes. With these properties, miRNAs can modulate mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 129 publications
0
27
0
Order By: Relevance
“…Mainly, when a tumor is more than 2 mm in diameter, it cannot grow further based on tissue penetration due to a hypoxic microenvironment of the tumor. Hence the tumor needs the formation of new blood vessels to supply oxygen and nutrients [ 36 ]. New vasculature is shaped in and around the tumor to allow it to grow exponentially.…”
Section: Vegf Family and Their Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mainly, when a tumor is more than 2 mm in diameter, it cannot grow further based on tissue penetration due to a hypoxic microenvironment of the tumor. Hence the tumor needs the formation of new blood vessels to supply oxygen and nutrients [ 36 ]. New vasculature is shaped in and around the tumor to allow it to grow exponentially.…”
Section: Vegf Family and Their Receptorsmentioning
confidence: 99%
“…Tumor hypoxia usually occurs during the anti-angiogenic period and is suspected to play a significant role in anti-angiogenic drug resistance [ 48 ]. Nevertheless, the long-term use of bevacizumab has some side effects, e.g., osteonecrosis [ 36 ].…”
Section: Possible Utilities Of Vegf Family Members In Colorectal Cancermentioning
confidence: 99%
“…14 15 Deregulation of the balance between above-mentioned factors causes pathologic conditions such as cancer development. 16 17 This hypothesis for the first time was described by Folkman. 18 Growing tumor cannot live without oxygen and nutrient.…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, a recent review cites studies that identified miR-1249, miR-126, miR-27b, 520a, miR-590-5p and miR-622 as inhibitors of angiogenesis in colorectal cancer (CRC). These miRNAs inhibit vascular endothelial growth factor A, whose elevated levels are closely related to CRC invasion and metastasis, through different pathways [259].…”
Section: Potential Role Of Exosomes In Cancer Treatmentmentioning
confidence: 99%